A global minimum wage formula as a proactive measure for climate migration - Derek Lough (Economics, Management and Sustainability)
On February 14, 2023, United Nations Secretary-General Antonio Guterres spoke to a global audience, stating, "The world will witness a mass exodus of entire populations on a biblical scale."